NEWSPAPERS EFFECT ON STUDENTS’ WRITING ACHIEVEMENT ACROSS ENGLISH PROFICIENCY LEVELS - Rizky Amelia; Abdul Muthim (Universitas Bengkulu, 2021)
Exposure is one of the obvious obstacles in the process of teaching and learning English. In figuring out one prospective exposure in students’ daily life, this study investigates the effect of newspapers as a medium in enhancing students’ English achievement, especially writing skill. The objective of this study is to find out whether students assigned to read English newspapers write better than those who are not. The subjects of the study were 85 English department students who were randomly assigned to an experimental group and a control group. A quasi-experimental was employed in this study. For six executive weeks, before the students were asked to write, the students in the experimental group were assigned to read English newspapers, whereas then students in the control group were not. By using Mann-Whitney and one-way ANOVA tests, the results of this study show insignificant results (0, 273; 0,194; and 0,179). As the high proficient students also could not take the newspapers for their learning benefits, affective and intrinsic factors such as awareness and willingness had to be considered.